The Numidian Sandstones in northern Morocco: Evidence for early Burdigalian autochthonous deposition on top of the Tanger Unit. (September 2021) - Abbassi, A.; Cipollari, P.; Zaghloul, M.N.; Cosentino, D.
Abstract: The Numidian Sandstones are widespread throughout the western Mediterranean, from Spain and North Africa to southern Italy. They consist of intercalations of thick ultra-mature sandstones within brownish shale deposits. Crucial issues about the Numidian Sandstones are still under debate, such as their pertinence to an undisputed paleogeographic domain and their age. In addition, in the Moroccan Rif, detailed sedimentological studies are still lacking, preventing the understanding of the main features of the sedimentary basin in which the Numidian Sandstones were deposited. This paper aims to reconstruct the Numidian Sandstone depositional environment via a detailed sedimentological study and provides new time constraints through quantitative analyses of calcareous nannofossil assemblages. The Numidian Sandstone sedimentary features suggest a depositional environment located in the transition between a lower muddy slope and a deeper basin plain. Quartz-rich sandy turbidites supplied sediments to this basin during a tectono-sedimentary event lasting ca. 1 Myr in the early Burdigalian. A key section from the Tanger Unit shows the Numidian Sandstones in stratigraphic continuity with the pre-Numidian deposits of the External Tanger Unit (Intrarif sub-domain). This evidence allows us to reject the notion of the Numidian Sandstones as a nappe, detached at their base from the pre-Oligocene deposits of the more internal units of the Flysch Basin. The new biostratigraphic analyses performed on the Numidian Sandstones from northern Morocco mostly correlate with the depositional age of the Numidian Sandstones outcropping in the rest of the Maghrebian Chain. The Numidian sand event, which affected the SW sector of the Mediterranean Basin from the Betics to the southern Apennines, was a unique and extensive event that was possibly triggered by the interplay among the uplift of the Atlas Chain, the sea-level drop at 20.4 Ma, and the establishment of a humid climate in North Africa at the beginning of the Miocene. Highlights: Calcareous nannofossil biostratigraphy constrains the age of the Numidian Sandstones in the Rif Belt. The Numidian Sandstones in the Rif Belt are early Burdigalian (20.4–19 Ma) in age. The Numidian Sandstones are channelized turbiditic flows sedimented on a muddy slope at the slope-to-basin transition. The Numidian Sandstones of northern Morocco pertain to the Tanger Unit.